Kehamilan Resiko Tinggi pada Ibu Primitua Sekunder Usia 38 Tahun: A Case Report - Dhita Amalya Reivanda; Nuryani Nuryani; Tutiek Herlina; Teta Puji Rahayu (CV. ITTC INDONESIA, 2026)
High-risk pregnancy is a pregnancy with one or more risk factors that may increase maternal and fetal complications. One of the major risk factors is maternal age ≥35 years with a pregnancy interval of more than 10 years (secondary primiparity). This case report aimed to describe comprehensive midwifery care for Mrs. W, a 38-year-old G3P2A0 woman with a high-risk pregnancy at PMB Bidan